Предмет: Алгебра,
автор: петушочек228
Разложить на множители x^9-x
Ответы
Автор ответа:
0
x^9-x=x(x^8-1)=x(x^4-1)(x^4+1)=x(x^2-1)(x^2+1)(x^4+1)=
=x(x-1)(x+1)(x^2+1)(x^4+1)
=x(x-1)(x+1)(x^2+1)(x^4+1)
Автор ответа:
0
Решение смотри в приложении
Приложения:
![](https://files.topotvet.com/i/dba/dba2e0fe1898ca62cfeaa8744006ec0e.jpg)
Похожие вопросы
Предмет: Английский язык,
автор: sofiaslepicko
Предмет: Английский язык,
автор: rayfovna
Предмет: Математика,
автор: dinadir
Предмет: География,
автор: Karina1504
Предмет: Алгебра,
автор: sveta14kr